Influences Of Psychosocial Support Services And Psychological Resilience On Health-Related Quality Of Life In Patients With Multiple Sclerosis In Kuwait - Alanezy, Mashail S. A. O. (2024)
Drawing upon the Locus Control Theory, Metatheory of Resilience and Resiliency, and Self-Determinant, this study examined the role of the psychosocial factors such as support services and resilience on health-related quality of life (HRQoL) and overall QoL of patients with multiple sclerosis (MS). A total of 230 PwMS treated in Ibn-Sina and al-Ameri hospitals in Kuwait participated in the study. This study uses both the disjoint two-stage approach of partial least squares – structural equation modeling (PLS-SEM) and multi-group analysis (MGA) to analyze the path model and compare the effects of psychosocial factors across male and female patients with MS.